2017
DOI: 10.1088/1757-899x/199/1/012101
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Power and Voltage Optimization Control Strategy in Active Distribution Network Based on the Determination of the Key Nodes

Abstract: Abstract.The distributed generation which is integrated in the active distribution network changes power flow, bringing new challenges to the voltage control. When voltage limit violation happens, in order to make the voltage return to normal range and improve the voltage quality, a novel voltage control strategy is proposed. Considering the voltage quality and node importance, the electrical closeness centrality and key node contribution degree are defined, and the key nodes are determined by the orders of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Kotenev et al [3] present a mathematical model to control reactive voltage on a node by using the synchronous motor excitation control. Meng et al [4] present a key node determination method to control reactive power and voltage optimization by compensation devices installed at the key nodes. Zechun and Mingming [5] choose the compensation nodes based on the sensitivity analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Kotenev et al [3] present a mathematical model to control reactive voltage on a node by using the synchronous motor excitation control. Meng et al [4] present a key node determination method to control reactive power and voltage optimization by compensation devices installed at the key nodes. Zechun and Mingming [5] choose the compensation nodes based on the sensitivity analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the traditional approach, the proposed optimization technique reported significant improvement in the voltage performance of the feeders as well as reduction of losses. In a related study, using the particle swarm optimization (PSO) method, a novel voltage control strategy was proposed in [9] to minimize power loss within a voltage optimization model. The results indicated that the proposed method was capable of solving the voltage violation issues, while also reducing the power loss and reasonably improving the voltage performance.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the proposed method was capable of solving the voltage violation issues, while also reducing the power loss and reasonably improving the voltage performance. These methods in [8,9], however, are based on heuristics and are incapable of providing viable solutions that deliver the optimal solution. In contrast to heuristic methods, mathematical optimization methods are able to consistently provide a guarantee on the optimality of the solution [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive power injection is also used for power stability, the synchronous motor excitation method at affected nodes was used by Kotenev et al [3]. A key node reactive power injection for voltage optimization is presented by Meng and Gao [4]. Zechun and Mingming [5] inject reactive power at nodes based on the sensitivity analysis.…”
Section: Introductionmentioning
confidence: 99%